2011
DOI: 10.1063/1.3557054
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electrocyclic ring opening of 7-dehydrocholesterol in solution: The influence of solvent on excited state dynamics

Abstract: Broadband UV-visible femtosecond transient absorption spectroscopy and steady-state integrated fluorescence were used to study the excited state dynamics of 7-dehydrocholesterol (provitamin D(3), DHC) in solution following excitation at 266 nm. The major results from these experiments are: (1) The excited state absorption spectrum is broad and structureless spanning the visible from 400 to 800 nm. (2) The state responsible for the excited state absorption is the initially excited state. Fluorescence from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(110 citation statements)
references
References 49 publications
9
98
1
Order By: Relevance
“…Aside from its obvious biological importance, Pro is a model system for understanding how to optically control polyene chromophores, which has potential applications in nanoscience. 52 This reaction has been studied both experimentally [53][54][55][56][57][58][59][60][61][62] and theoretically. [63][64] Critical points on Pro potential energy surfaces are represented in Figure 1 (SA-3-CAS(6,4)/6-31G, see SI for details and validation of the electronic structure employed).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from its obvious biological importance, Pro is a model system for understanding how to optically control polyene chromophores, which has potential applications in nanoscience. 52 This reaction has been studied both experimentally [53][54][55][56][57][58][59][60][61][62] and theoretically. [63][64] Critical points on Pro potential energy surfaces are represented in Figure 1 (SA-3-CAS(6,4)/6-31G, see SI for details and validation of the electronic structure employed).…”
mentioning
confidence: 99%
“…67 More recently, Tang et al employed ultrafast UV-vis transient absorption spectroscopy to demonstrate that the photoconversion of Pro to Pre exhibits biexponential decay, with time constants ranging from 0.39-0.65ps and 1.06-1.81ps depending on the solvent. 59 Tapavicza et al comprehensively studied the photochemistry of Pro and Pre using TSH coupled to LR-TDDFT. 64 At variance with experimental results, the computed reaction rates are too fast and the population decay is not biexponential.…”
mentioning
confidence: 99%
“…Interestingly, nonexponential depopulation of state 1B was suggested more than 20 years ago based on the analysis of the absorption line shapes and resonance Raman intensities in CHD [129]. Sension and co-workers have also raised the possibility that non-exponential relaxation dynamics are at work in provitamin D [134]. Pronounced non-exponential internal conversion dynamics is apparently a general property of this class of molecules.…”
Section: Photochemical Insightsmentioning
confidence: 96%
“…The framework for thinking about these two molecules is owed to earlier work in which femtosecond transient absorption spectroscopies were employed [67,[121][122][123][124][125][126][127][128][129][130][131]. In particular, Sension and co-workers have conducted rigorous studies on CHD and a number of its derivatives in solution (e.g., alphaphellandrene, a-TP) [126,128,134,135]. This group has also shown that the basic physics translates to larger systems with cyclic diene moieties such as provitamin D [135][136][137].…”
Section: Probing Ultrafast Excited State Dynamics In Ring Opening Sysmentioning
confidence: 97%
“…Pre itself plays the central role, as it reacts to four distinct main Vita photo isomers (DPI) Pro, Lumi, and Tachy and toxisterols (Toxi). While the provitamin D ringopening and its analogous reaction in cyclohexadiene has been studied extensively, both theoretically [17][18][19][20] and experimentally, 18,[21][22][23][24][25][26] little research has been done to assess the influence of tachysterol on photochemical vitamin D production. In particular, its excited state dynamics has neither been investigated by experiments nor by simulations.…”
Section: Introductionmentioning
confidence: 99%